SYNERGISTIC AND ANTAGONISTIC EFFECTS ON ANTIMICROBIAL PROPERTIES OF ORGANIC AND AQUEOUS EXTRACTS OF BACILLUS CLAUSII KP10 IN COMBINATION WITH CONVENTIONAL ANTIBIOTICS - S. Kabeer; Z. Mushtaq (Journal of Animal and Plant Sciences, 2023)
Due to emergence of multidrug resistance, alternative approaches are practiced and needed in conventional antimicrobial therapies. Drug combination therapies have been used like synergism for better results with decreased drug dosage to avoid toxicity than monotherapy, but results can be additive and antagonistic depending on their combined effect. The present project was therefore designed to assess the effects of already reported bioactive fractions of B.clausii KP10 with each other and with antibiotics in synergistic manner to combat microbes. Different solvents were used for the extraction and fractionations. Antimicrobial activities were performed against different available bacterial and fungal strains. In our experiments crude methanolic extract (CME), n-hexane fraction (n-HF), chloroform (CLF), ethyl acetate (EAF), Methanol Soluble (MSF) and water soluble fractions (WSF) were obtained and then combinations of each were prepared with (1:1, v/v) each other and with reported antibacterial and antifungal drugs streptomycin (STM) and Terbinafine (TER) separately (1:1:1). Single extract with drug combination was also prepared (1:1). Maximum zone of inhibition was shown by combination of n-HEF:MSF (24 mm) against S. aureus. CLF:WSF:STM showed maximum ZOI (37.2 mm) against E. coli. WSF: STM showed maximum ZOI (33 mm) against S. aureus. Maximum antifungal activity was shown by CME:WSF:TER (26 mm) and EAF:TER with maximum ZOI (17 mm) against Fusarium solani. n-HEF:EAF:TER showed maximum ZOI (18 mm) against Aspergillus niger. Combination of extracts with each other usually showed antagonistic behavior but extracts with standard drugs have shown synergy which could be a better approach in the development of antimicrobials therapies.
Keywords: Antagonistic; Antimicrobial; Bacillus clausii KP10; Bioactive compounds; Synergistic